Development of Science-Islamic Integrated Disaster Geography Textbooks and Effect on Students’ Learning Outcomes - Imam Wahyu Hidayat; Saiful Amin; Ramadhani Lausi Mkumbachi; Wulan Nurus Shobah; Renata Tiand Indriansyah; Muchammad Akbar Kurniawan (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Islamic university students in Indonesia must improve disaster literacy by developing science-Islamic integrated disaster geography textbooks. This study aims to determine the appropriateness of science-Islamic integrated disaster geography textbooks and the effect of using them on students’ learning outcomes. The Dick and Carey model was used in this development. The product was validated by experts in material, design, and the integration of Islamic science and tested on students and lecturers on a limited basis. The experiment subjects were 27 Social Science Education students from Universitas Islam Negeri Maulana Malik Ibrahim Malang. Instruments are in the form of a questionnaire to determine the appropriateness of the book and test questions to determine the effect of book products on learning outcomes. Data were analyzed descriptively and using an independent sample t-test. The results showed that science-Islamic integrated disaster geography textbooks were appropriate for use in learning with an effective category (appropriateness score = 81.08%). The use of science-Islamic integrated disaster geography textbooks affected students’ learning outcomes (p=0.000) < α=0.05). Further research suggests developing digital books on other materials because the Islamic science integration curriculum has been proven to improve students’ learning outcomes in Islamic universities.